Evaluasi Program Bantuan Operasional Sekolah (BOS) Pada SMP Negeri 6 Salatiga Menggunakan Discrepancy Evaluation Model (DEM) - Ulya Setya Ningsih; - Mawardi; Bambang Ismanto (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
This is an evaluation study for the School Operational Subsidy (SOS) program at SMP Negeri 6 Salatiga to identify the aspects of the design, installation, process, product, and cost benefit analysis. Using the Discrepancy Evaluation Model (DEM), the subjects who participated were school committee members, school principals, treasurers, teachers and parents. The instruments were interview sheets, observation guidelines, and document study guidelines. The data analysis was done with percentage and categorical techniques. The results showed that: 1) in the design aspect, there was a 5% average gap between the standards set and the actual conditions of the program implementation, in very low category; 2) in the installation aspect, there was 0% or no gap between the standards set and the reality that occurs empirically; 3) in the process aspect, there was an average gap of 4%, in very low category; 4) in the product aspect, there was an average gap of 13%, in very low category; and 5) aspects of the cost benefit analysis, there was an average gap of 11% in very low category.